Lesão intra-epitelial e DNA-HPV anal e fatores de risco associados em mulheres com lesão intra-epitelial genital HPV induzido - Benício, Givanildo Carneiro (2013)
The anal cancer, which corresponds to 4% of all malignant neoplasms of the lower digestive tract, has been associated with HPV. There is a predominance of anal cancer in women (1.5 out of 5 times). The objectives of the study were: to evaluate the frequency of low and high oncogenic risk DNA-HPV, and of anal intraepithelial atypia in liquid-based cytology (SurePath BD) among immunocompetent women with genital intraepithelial lesions, and to identify the related risk factors. A prospective controlled study of quantitative, exploratory and descriptive nature was conducted in the clinic of Maternidade Escola Assis Chateaubriand (Maternity School) of the Ceará Federal University from August 2011 to September 2012. One hundred and fifty women submitted to genitoscopy in the Clinic of Lower Genital Tract Pathology and Colposcopy (PTGIC) with a history of HPV-induced lesions were included in the study. A standard questionnaire was applied. The patients underwent the procedure of anal cytology collection using the kit of SurePath liquid-based cytology (BD®) and then the samples were sent to the cytopathology laboratory for cytology slides preparation and DNA-HPV detection through the 2nd generation Hybrid Capture method. The data were analyzed using GraphPad Prism 6.0 software, applying the Student t test for nominal variables and the Fisher exact test for quantitative variables. The age ranged from 17 to 68 years (mean = 33.8 + 14.28) in the study group including women with genital intraepithelial lesions and from 19 to 75 years (mean = 40.48 + 15.1) in the control group with women with no genital lesion. The practice of anal intercourse occurred in 44 (55%) women in the study group and 34 (48.7%) in the control group. Analyzing the cytological atypia (ASC-US and LSIL), 30% of women with genital HPV lesions showed the presence of changes in cells of the anal canal. Lesions of perineum and perianus (p = 0.0003), vulva (p = 0.0157) and uterine cervix (p = 0.0223) were associated with anal cytological atypia. There was no significant association between DNA-HPV in the groups. It is concluded that the anal cytological atypia was frequent among women with perianal, vulva and uterine cervix lesions suggesting the need for screening anal intraepithelial lesions among immunocompetent individuals.